INTEGRATING THE QUANTUM MAKKY METHOD AND INDIVIDUAL COUNSELING: AN EDUCATIONAL INNOVATION FOR ENHANCING MEMORIZATION AND COMPREHENSION - Sallsa Nurajijah; Nur Hermatasiyah; Pebrisa Amrina (CV. TOTUS TUUS, 2025)
Memorizing the Qur'an is a core tradition in Islamic education, promoting spiritual growth and the preservation of divine revelation. However, traditional rote memorization methods often overlook individual learning styles and emotional barriers, leading to challenges in long-term retention and comprehension. This study aimed to evaluate the effectiveness of the Quantum Makky method combined with individual counseling in enhancing the memorization and understanding of Qur'anic verses, specifically Surah An-Naba (verses 4, 5, and 6) at Rumah Tahfiz Mafaza 3. Using a qualitative case study approach, data were collected through observations, in-depth interviews, and documentation, then analyzed using thematic analysis to identify key patterns. The findings revealed that Quantum Makky gestures significantly improved memory retention by creating strong cognitive links between physical movements and textual meanings. For instance, using a single finger to denote certainty in verse 4 (كَلَّا سَيَعْلَمُونَ) and spreading hands to symbolize the earth's vastness in verse 6 (أَلَمْ نَجْعَلِ الْأَرْضَ مِهَادًا) effectively reinforced the memorization process. Additionally, individual counseling addressed psychological barriers, enhancing self-confidence, learning motivation, and emotional resilience. This approach resulted in notable improvements in four areas: memory retention, comprehension, learning motivation, and public recitation confidence. The study highlights the value of integrating multisensory learning with personalized support, providing a practical framework for enhancing cognitive retention and emotional resilience in Qur'anic education. Future research should explore the scalability of this approach and consider integrating digital tools for broader application.